Meningkatkan Aktivitas Belajar Matematika dengan Metode Means Ends Analysis pada Siswa Kelas X MA Darussalam - Azwan Anwar; Anriani Anriani; Rahmah Mustafa; Nur Aisyah; Nursamsi Nursamsi (Lembag, 2024)
This research is classroom action research (PTK) carried out at MA Darusslam Manuju District. Gowa which aims to improve Mathematics Learning Activities Using the Means Ends Analysis Method. The subjects of this research were class X students. Data were collected using student activity observation sheets. The collected data was analyzed using quantitative and qualitative analysis. The results of the research showed that the average percentage of student activity in cycle I was 29.63% with a little category. and in cycle II it was 55.73% in the many category. So an increase of 26.1% was obtained. These results can be concluded that there has been an increase in Mathematics Learning activities using the Means Ends Analysis Method.